New cognition on pore structure characteristics of Permian marine shale in the Lower Yangtze region and its implications for shale gas exploration - Wenbo Zhu; Xunhua Zhang; Daorong Zhou; Chaogang Fang; Jianqing Li; Zhengqing Huang (Natural Gas Industry B, 2021)
Shale of the Middle–Upper Permian Dalong Formation and Gufeng Formation in the Lower Yangtze region is characterized by large thickness, high total organic carbon (TOC), wide distribution and moderate organic thermal evolution degree, so it may be the next important field of shale gas exploration. In order to point out the target and direction of shale gas exploration and development in this region, this paper selects the Dalong Formation and Gufeng Formation shale in the Xuanjing area of Lower Yangtze as the research object to quantitatively describe the development characteristics of shale pores of different scales by means of scanning electron microscopy (SEM), high pressure mercury injection, CO2 and N2adsorption. Then, the fractal dimension of sample pores is calculated by using the FHH (Frenkel–Halsey–Hill) model. Finally, combined with TOC and mineral compositions, the relationship between pore structure and fractal dimension is discussed. And the following research results are obtained. First, dominant lithofacies of Dalong Formation are argillaceous-rich siliceous shale and argillaceous-rich/siliceous mixed shale, which has smaller specific surface area and pore volume, larger average pore diameter. The pore development is mainly controlled by clay mineral content. Dominant lithofacies of Gufeng Formation is siliceous shale, which has a larger specific surface area and pore volume, and smaller average pore diameter. The pore development is controlled by organic matter and brittle mineral content. Second, the influencing factors of fractal dimension can be attributed to the controlling factors of micropore development. The fractal dimension D1of Dalong Formation ranges from 2.4515 to 2.5513 (average 2.5227), and D2ranges from 2.5817 to 2.6578 (averagely 2.6246). The fractal dimension D1of Gufeng Formation ranges from 2.5817 to 2.6578 (averagely 2.6246), and D2ranges from 2.7227 to 2.871 (averagely 2.813). Gufeng Formation shale presents the characteristics of more complex pore structure. Third, the fractal dimension D1is more sensitive to specific surface area, pore development and mineral composition, while D2is more effective in characterizing the average pore diameter. In conclusion, Dalong Formation shale with high D1and D2and Gufeng Formation shale with low D1and high D2can be taken as the favorable exploration targets of Permian marine shale gas in the Lower Yangtze region, and the regional overpressure zones (belts) with weaker structural deformation in hydrocarbon rich sags will be the favorable shale gas exploration targets in this area.